Analisis Penyebab Degradasi Moral Remaja (Studi di Desa Sukamaju Kecamatan Nyalindung Kabupaten Sukabumi) - Hoerudin Hoerudin; Yanti Amalia Afifah; Sugenda Sugenda (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
The aim of this research is to determine the causes of moral degradation of teenagers in Sukamaju Village, Nyalindung Sukabumi District. This research uses a qualitative approach with descriptive methods. Data collection was carried out by observation, interviews and documentation. Data sources consist of teenagers aged 18 -23 years, the community, parents and community leaders in Sukamaju Village, Nyalindung District. The results of this research are (1) The forms of moral degradation of teenagers in Sukamaju village, Nyalindung sub-district are: minor delinquency, for example being stubborn, not wanting to obey parents and teachers, running away (truant) from school, not wanting to study, often fighting, likes to talk. impolite words, how to dress and act like you don't care and so on. (2) The factors that cause the moral degradation of teenagers in Sukamaju village, Nyalindung sub- district are: Lack of instillation of the spirit of religion in each person in society. (3) The impact of moral degradation in Sukamaju Village, Nyalindung Subdistrict is: the development of a culture of violence making it vulnerable to conflict between groups in society. (4) The role of the family in the moral degradation of teenagers in Sukamaju Village, Nyalindung Subdistrict, namely: teaching religious education. (5) Efforts to overcome the moral degradation of teenagers in Sukamaju Village, Nyalindung District, namely: It is necessary to conduct a filter or selection of incoming foreign culture, so that negative elements can be avoided.